TINGKAT PENGETAHUAN DAN SIKAP PENGGUNAAN ANTIBIOTIK DI FASILITAS PELAYANAN KESEHATAN INDONESIA - Dewi, Eva Rosdiyana; Wahyuningsih, Sri (Jurnal Buana Farma, 2025)
Inappropriate antibiotic use can lead to bacterial resistance, a serious global issue including in Indonesia. The level of public knowledge and attitudes regarding antibiotic utilization are crucial factors in controlling the occurrence of resistance. This literature review aims to assess the community's level of knowledge and attitudes toward antibiotic use in Indonesia, as well as the influencing factors. The methodology employed is a literature study, with data collected through electronic databases such as Google Scholar, PubMed, and ScienceDirect, using keywords like "knowledge," "attitude," "antibiotics," and "resistance" from 2015 to 2025. A total of 10 articles meeting the inclusion criteria were systematically explored, depicting various community experiences across different regions of Indonesia. The results indicate that public knowledge about antibiotics varies from low to adequate, depending on demographic factors such as educational level and personal experience. Additionally, improper attitudes, such as easily requesting antibiotics without a prescription, are closely related to a lack of understanding regarding indications and potential adverse outcomes. Demographic factors like education level, age, and income significantly influence community knowledge and attitudes toward antibiotic use. This review underscores the need for consistent and informative educational interventions through healthcare facilities to improve knowledge and motivate rational behavior regarding antibiotic use.